2021
DOI: 10.1038/s41591-020-1142-7
|View full text |Cite
|
Sign up to set email alerts
|

A neuroimaging biomarker for sustained experimental and clinical pain

Abstract: Peer review information Jerome Staal and Kate Gao were the primary editors on this article and managed its editorial process and peer review in collaboration with the rest of the editorial team. Reprints and permissions information is available at www.nature.com/reprints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
130
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(154 citation statements)
references
References 67 publications
3
130
1
1
Order By: Relevance
“…Third, while our tonic heat pain paradigm models some aspects of a sustained pain experience, 31 tonic pain is not identical with chronic pain. It is conceivable that tACS may not modulate pain in healthy participants but only in patients when altered neural circuits can be restored, for example by reversing a slowing of the dominant frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Third, while our tonic heat pain paradigm models some aspects of a sustained pain experience, 31 tonic pain is not identical with chronic pain. It is conceivable that tACS may not modulate pain in healthy participants but only in patients when altered neural circuits can be restored, for example by reversing a slowing of the dominant frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Analytic approaches can also improve reliability, with multivariate markers likely providing a broader base of support relative to single regions of interest 6,55 . In addition, methods for improved inter-subject alignment 56,57 and systematic approaches for developing biomarker pipelines 58,59 will improve performance. Finally, spatial resolution is an additional consideration, especially for smaller structures like the amygdala, and effective resolution will be determined by the smoothing kernel applied.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these authors show that by comparison, relying on static changes (e.g. static correlation averaged over scan duration) alone had lower predictive accuracy & had poor crossvalidation performance (Lee et al 2021).…”
Section: Pain Related Changes In Cbf Dynamicsmentioning
confidence: 98%
“…2016). A recent paper by Lee et al (2021) supports this by identified a neuroimaging biomarker for sustained experimental and clincal pain by focusing on dynamic changes in brain function (Lee et al 2021). Here, by using multiple BOLD FMRI datasets these authors employ a rigorous, data-driven approach to build a predictive algorithm for both experimental tonic and clinical pain that is based on whole-brain dynamic connectivity changes.…”
Section: Pain Related Changes In Cbf Dynamicsmentioning
confidence: 99%